Impact of the COVID-19 pandemic on gastrointestinal endoscopy in the Netherlands: analysis of a prospective endoscopy database - Lantinga, Marten A.; Theunissen, Felix; ter Borg, Pieter C. J.; Bruno, Marco J.; Ouwendijk, Rob J. T.; Siersema, Peter D.; on behalf of the Trans.IT foundation study group (Endoscopy, 2020)
Background COVID-19 has dramatically affected gastrointestinal endoscopy practice. We aimed to investigate its impact on procedure types, indications, and findings. Methods We retrospectively analyzed endoscopies performed in 15 Dutch hospitals by comparing periods 15 March to 25 June of 2019 and 2020 using the prospective Trans.IT database. Results During lockdown in 2020, 9776 patients underwent endoscopy compared with 19 296 in 2019. Gastroscopies decreased by 57 % (from 7846 to 4467) and colonoscopies by 45 % (from 12219 to 5609), whereas endoscopic retrograde cholangiopancreatography volumes remained comparable (from 578 to 522). Although endoscopy results indicative of cancer decreased (from 524 to 340), the likelihood of detecting cancer during endoscopy increased (2.7 % [95 % confidence interval (CI) 2.5 – 3.0] in 2019 versus 3.5 % [95 %CI 3.1 – 3.9] in 2020; P < 0.001). After lifting of lockdown, endoscopy volumes started to return to normal, except for colorectal cancer screening. Conclusions Fewer endoscopies were performed during the COVID-19 lockdown, leading to a significant reduction in the absolute detection of cancer. Endoscopies increased rapidly after lockdown, except for colorectal cancer screening.